Concurrent Ligament and Meniscal Injuries in a 27Year Old Male,Management through Acupuncture an d Cold Knee Pack: A Case Report - Dharuman, Annamalai; N, Prabu; S, Geethanjali; V, Madhumitha; CP, Syam Kumar; B, Abirami (Indian Journal of Integrative Medicine, 2024)
Multiple ligament knee injuries are complex and challenging conditions that often result in long term impairment and reduced quality of life for those affected. These injuries commonly involve damage to two or more of the knee’s prima ry stabilizing structures, including the anterior cruciate ligament, posterior cruciate ligament, medial collateral ligament, and lateral collateral lig ament. The management of such injuries remains a topic of debate in healthcare. Electro acupuncture and cold packs, a non pharmaceutical treatment modality, have shown promising results in the management of musculoskeletal conditions, including ligament injuries . A 27 year old patient with concurrent ligament and meniscal injuries, mostly Grade 2 multiple li gament injuries, was given electroacupuncture and a cold knee pack 5 times a week for 2 months. The needles used were disposable, sterile, stainless ste el 0.25mm x 25mm to a depth of 20 25mm and were inserted perpendicularly at Gall Bladder 34, Spleen 9, S pleen 10, Urinary Bladder 40, and Kidney 3 bilaterally. Gall Bladder 34 and Spleen 9 were connected to electroacupuncture for 20 minutes with continuou s stimulation. Followed by a cold knee pack, a 5 feet long, 5 inch wide white cotton cloth dipped in cold water (55º to 65º F), wrapped around the knee, and then covered with a similarly sized woollen cloth for 20 minutes. Results show that after 2 months of tr eatment, the Visual Analogue Scale (VAS) reduced pain from 8 to 0. The lateral and medial stress tes ts are negative. Magnetic Resonance Imaging (MRI) shows that grade 2 medial collateral ligament injuries become completely normal. Electroacupuncture and cold kn ee packs show promising pain reduction and promote healing.